ANALISIS EFEKTIVITAS KEGIATAN PRAKTIKUM SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR MAHASISWA - Dwi Wahyudiati (Jurnal Tatsqif, 2016)
The current research intends to clarify the lab activities program of Basic Chemistry course (including its planning and implementation) at Science Education Department of IAIN Mataram and the factors affecting the quality of the program in order to maximize students’ learning achievement. It is a qualitative research where that data are obtained from students, lecturers, and laboratory assistances. The research found the following remarks: 1) the planning process shows that students have weaknesses on their understanding of the topic being practiced, their capability on using the tools and stuff used in the practices, and on the quantity of consultation to laboratory assistances; 2) During the implementation process, there some blind spots such as inadequate equipment to do lab activities, students’ difficulties in compiling report, unsynchronized schedule of lab activities, and inadequate explanation and consultation to supporting lecturers and laboratory assistances. To anticipate the problems above, an intensive evaluation is held together with students, laboratory assistances, and supporting lecturers to optimize their roles. The factors contributing to the quality of the lab activity are student motivation, the lecturers and laboratory assistances contributions, and the lab equipment.